Experience of parents of children with congenital heart disease: feelings and obstacles - Thaís Sena Mombach Barreto; Victória Tiyoko Moraes Sakamoto; Jardel Scremin Magagnin; Débora Fernandes Coelho; Roberta Waterkemper; Simone Travi Canabarro (Rev Rene)
Objective: understand the meaning of the experiences of parents of children with congenital heart disease regarding feelings, obstacles and expectations. Methods: exploratory qualitative study conducted at a pediatric intensive care unit of a reference hospital. Participants corresponded to seven mothers and four fathers of children with congenital heart defect, surgically corrected and with more than 8 hours of admission, totalling 11 participants.  Data collection was performed through semi-structured individual recorded interviews. Data were described according to thematic content analysis. Results: five thematic categories emerged: (1) unpreparedness to face the problem; (2) feelings involved (3) factors that make difficult to face the problem; (4) factors that facilitate facing the problem; (5) spirituality. Conclusion: each family is unique and needs support to better face the disease and its process. It is essential to develop interdisciplinary network support, providing comprehensive care.